Assessment of quality of life and supportive care in women with - Eghtedar, Samereh; Moghadasyan, Sima; Ebrahimi, Hosein; Haydari, Shiva (Advances in Nursing & Midwifery, 2012)
Abstract Background and Aim : The diagnosis of breast cancer is very stressful event having extensive impact on different aspects of daily life and increase the need for support from care providers. The aim of this study was to examine the association between quality of life and supportive care in women with breast cancer. Materials and Methods: A descriptive - correlational design was used for this study. One hundred patients with breast cancer, who attended to clinic of Hematology and Oncology in Tabriz University of Medical Sciences, participated in this research. The sample of the study consisted of 100 women with breast cancer who were selected by judgmental sampling .Data was collected using a validated questionnaire consisting of 3 parts: socio–demographic and clinical characteristics, quality of life and nursing supportive care. Validity of the questionnaire was obtained by content validity. Reliability was assessed through Cranach’s alpha. Data were analyzed by SPSS statistical software (version 14. Results : Mean age of participants was 45.78±8.99 , a majority of the participants (21%) were between 35 to 39 years of age .The duration of illness was 1 to 4 years in 50% of the participants(M=2.08, SD=1.46) . 63.6% of participants reported that they receive moderate supportive care from nurses . Overall quality of life was undesirable in 52.5% of the women. Finding indicated a direct and significant association between quality of life scores and supportive care(r=0.2 P<0.05) Conclusion : Cancer and its treatment influence integrity of person. The results of this study can help nurses in their supportive care. By providing supportive care , nurses can promote the quality of life of breast cancer patients.